Electronification of Civil Justice in Lithuania - Nekrošius, Vytautas; Simaitis, Rimantas; Vėbraitė, Vigita; Brazdeikis, Aurimas (Wydawnictwo C.H. Beck, 2017)
The purpose of this article is to focus and explain the most important initiatives in Lithuania to introduce and promote electronification of civil proceedings in Lithuania. The authors will discuss the most important advantages and the biggest problems regarding digitalisation of civil justice in Lithuania.
Keywords: civil justice; modern technologies; Lithuania